ANALISIS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KECERDASAN EMOSIONAL SISWA PADA ERA NEW NORMAL DI SEKOLAH MENENGAH PERTAMA WAHID HASYIM MALANG - Dzullhijj Dima Nabila; Maskuri Bakri; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
PAI learning has a goal that is in line with national goals in which it forms emotional intelligence but in practice PAI learning has not been carried out optimally, the most frequent problem is the delivery of which only transfers knowledge without any additional habituation or programs in forming emotional intelligence. Coupled with the adjustment of conditions and situations in the New Normal Era, the process of PAI Learning activities in practice needs to have a learning design with adequate characteristics and strategies, not only that PAI learning processes and models are able to shape aspects of emotional intelligence. qualitative The type of research used is descriptive research. Data collection techniques used by researchers are observation, interviews and documentation. After collecting the data, the data analysis technique used data condensation, data presentation and drawing conclusions. The results showed that the PAI learning design in the new normal era had 2 different implementation designs when PPKM and PTMT, resulting in differences in the learning process, and the application of the PAI learning model in the new normal era at Wahid Hasyim Middle School using the Contextual model (CTL) when PPKM and Cooperative model when PTMT. And the cooperative learning model that can shape students' emotional intelligence in various aspects at Wahid Hasyim Middle School